2013
DOI: 10.1002/adfm.201300437
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Stabilization by Supramolecular Perfluorophenyl‐C60 Interactions Leading to Efficient and Thermally Stable Organic Photovoltaics

Abstract: A new PC61BM‐based fullerene, [6,6]‐phenyl‐C61 butyric acid pentafluorophenyl ester (PC61BPF) is designed and synthesized. This new n‐type material can replace PC61BM to form a P3HT:PC61BPF binary blend or serve as an additive to form a P3HT:PC61BM:PC61BPF ternary blend. Supramolecular attraction between the pentafluorophenyl group of PC61BPF and the C60 cores of PC61BPF/PC61BM can effectively suppress the PC61BPF/PC61BM materials from severe aggregation. By doping only 8.3 wt% PC61BPF, device PC61BPF651 exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 97 publications
1
33
0
Order By: Relevance
“…Mediated by the designed oligothiophene-fullerene derivatives, they helped the organization of P3HT phase and constrained the PC61BM diffusions by reducing the P3HT/PC61BM surface energy (Figure 7a). It efficiently led to remarkably improved PCE up to 4.37% and little loss after thermal annealing test at 150 °C for 10 h. Similar effects were discovered by Liao et al who developed fullerene derivative: [6,6]phenyl-C61 butyric acid pentafluorophenyl (PC61BPF) bearing pentafluorophnyl group [60]. The pentafluorophenyl group with the PC61BM cages formed a supermolecule, which imparted restriction to the thermal-driven diffusion during thermal aging (Figure 7b).…”
Section: Small Moleculessupporting
confidence: 50%
“…Mediated by the designed oligothiophene-fullerene derivatives, they helped the organization of P3HT phase and constrained the PC61BM diffusions by reducing the P3HT/PC61BM surface energy (Figure 7a). It efficiently led to remarkably improved PCE up to 4.37% and little loss after thermal annealing test at 150 °C for 10 h. Similar effects were discovered by Liao et al who developed fullerene derivative: [6,6]phenyl-C61 butyric acid pentafluorophenyl (PC61BPF) bearing pentafluorophnyl group [60]. The pentafluorophenyl group with the PC61BM cages formed a supermolecule, which imparted restriction to the thermal-driven diffusion during thermal aging (Figure 7b).…”
Section: Small Moleculessupporting
confidence: 50%
“…Introducing compatibilizers, such as small molecules, end‐capped polymers, and copolymers, into the BHJ system is another effective method to reduce surface energy mismatching between the BHJ materials and impede the large‐size phase separation of the BHJ films. An example can be found in the work of Sivular et al, where amphiphilic diblock copolymer compatibilizers reduce the interfacial energy between immiscible BHJ components and stabilize the film morphology against destructive thermal phase segregation .…”
Section: Device Stabilitymentioning
confidence: 99%
“…It has also been demonstrated that a newly designed P3HT‐ graft ‐poly(2‐vinylpyridine) (P3HT‐ g ‐P2VP) polymer can be used as an effective compatibilizer to fabricate thermally stable OSCs by inducing desirable segregation with broader interfacial width and lower interfacial tension . Recently, Liao et al and Wang et al revealed that supramolecular interactions based on π–π interactions or van der Waals forces between compatibilizers and fullerene derivatives can suppress fullerene aggregation and realize thermal stability of a BHJ film. Liao et al designed a new fullerene derivative, [6,6]‐phenyl‐C 61 butyric acid pentafluorophenylester (PC 61 BP F ), and confirmed that thermally stable OSCs can be achieved via supramolecular interactions between the pentafluorophenyl groups and the fullerene core .…”
Section: Device Stabilitymentioning
confidence: 99%
“…The use of nonsolvent additives can improve the thermal stabilities of BHJ films . Cheng et al added two crosslinkable fullerene derivatives PCBSD and PCBS to a P3HT:PC 60 BM blend; PC 60 BM diffuses out of this polymer matrix and aggregates to form large PC 60 BM clusters or single crystals at high temperatures .…”
Section: Morphology Controlmentioning
confidence: 99%